Sub-chronic nicotine exposure influences methamphetamine self-administration and dopamine overflow in a sex-and genotype-dependent manner in humanized CHRNA6 3′-UTR SNP (rs2304297) adolescent rats - Carreño, Diana; Facundo, Antonella; Cardenas, Anjelica; Lotfipour, Shahrdad (Frontiers in Pharmacology, 2024)
The rewarding effects of drugs of abuse are associated with the dopaminergic system in the limbic circuitry. Nicotine exposure during adolescence is linked to increased use of drugs of abuse with nicotine and methamphetamine (METH) commonly used together. Nicotine acts on neuronal nicotinic acetylcholine receptor (nAChR) systems, critical for reward processing and drug reinforcement, while METH leads to a higher dopamine (DA) efflux in these brain regions. A human single nucleotide polymorphism (SNP) in the 3'-untranslated region (UTR) of the α6 nicotinic receptor subunit gene (CHRNA6, rs2304297), has been linked with tobacco/nicotine and general substance use during adolescence. Using CRISPR-Cas9 genomic engineering our lab recapitulated the CHRNA6 3'UTR C123G SNP, generating 𝛼6 CC and 𝛼6 GG allele carriers in Sprague Dawley rats. We hypothesized the CHRNA6 3'UTR C123G SNP would sex-and genotype-dependently enhance nicotine-induced METH self-administration as well as nicotine-induced DA overflow in the nucleus accumbens shell of adolescent 𝛼6 GG and 𝛼6 CC carriers. Methods: Adolescent male and female rats underwent a 4-day subchronic, low-dose (0.03 mg/kg/0.1 mL, x2) nicotine pretreatment paradigm to assess intravenous METH (0.02 mg/kg/0.1 mL) self-administration as well as nicotine-and METH (0.02 mg/kg/0.1 mL)induced DA overflow in the nucleus accumbens shell (NAcS) using in vivo microdialysis coupled with high-performance liquid-chromatography-electrochemical detection (HPLC-ECD). Results: Nicotine pretreatment sex-and genotype-dependently enhanced subsequent METH self-administration in adolescent CHRNA6 3'UTR C123G SNP rats. Further nicotine and METH-induced DA overflow is observed in 𝛼6 CC females as compared to 𝛼6 GG females, with METH-induced DA overflow enhanced in 𝛼6 GG males when compared to 𝛼6 CC males. Conclusion: These findings demonstrate that the CHRNA6 3'-UTR C123G SNP can sex-and genotype-dependently impact adolescent nicotine-induced effects on METH self-administration and stimulant-induced DA overflow in reward regions of the brain.